2016
DOI: 10.1002/ajoc.201600296
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Mediated Phosphonylation of C(sp2)−H Bonds with P−H Bonds: Direct C−H Functionalization of Ferrocenyl Anilides and Dialkyl Phosphites under Palladium‐ and Copper‐Free Conditions

Abstract: Ad irect, silver-mediated CÀHp hosphonylation reaction of ferrocenyl anilides and dialkyl phosphites was developed. Thism ethodology can tolerate av ariety of func-tional groups and is free of palladium and copper. Moreover, mechanistic studies have revealed that the reaction pathway is of ar adical type.Supportinginformation for this article can be found under http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Accordingly, the chemical reactivity of the organophosphorus compounds can be influenced by their structural geometry and valency of the phosphorus atom. For example, H -phosphonates with P(O)H bonds are commonly used as starting materials for P-C bond formation and thus their chemical reactions have been investigated in detail [ 6 , 9 , 12 , 24 , 25 , 29 , 30 , 31 , 33 , 34 ]. It is reported that presence of the P=O bond is the driving force for their reactions [ 23 ].…”
Section: General Principles Of P-c Bond Formationmentioning
confidence: 99%
“…Accordingly, the chemical reactivity of the organophosphorus compounds can be influenced by their structural geometry and valency of the phosphorus atom. For example, H -phosphonates with P(O)H bonds are commonly used as starting materials for P-C bond formation and thus their chemical reactions have been investigated in detail [ 6 , 9 , 12 , 24 , 25 , 29 , 30 , 31 , 33 , 34 ]. It is reported that presence of the P=O bond is the driving force for their reactions [ 23 ].…”
Section: General Principles Of P-c Bond Formationmentioning
confidence: 99%
“…In 2015, Yuan et al [102] developed the silver-catalyzed direct C(sp 2 )-H radical phosphorylation of coumarins with H-phosphites, affording selective coumarin-3-yl phosphonate in moderate to good yields. In 2016, a silver-mediated C-H phosphonylation reaction of ferrocenyl anilides with dialkyl phosphites was developed [Figure 67] [103] . The method is free of palladium and copper catalysts and tolerates a variety of functional groups.…”
Section: Dehydrogenative C-h Phosphorylationmentioning
confidence: 99%
“…[11] Lanthanide elements are the treasure house of multifunctional materials with excellent magnetic, optical, and electrical properties. [12][13][14][15] However, new non-centrosymmetric (NCS) lanthanide compounds are hard to obtain because the high coordinated lanthanide polyhedrons are preferred to form CS infinite frameworks. As the retrieved result from the Inorganic Crystal Structure Database, the proportion of NCS compounds in lanthanide oxides is ≈12.4%, which is far lower than that in all inorganic compounds (≈18%).…”
Section: Introductionmentioning
confidence: 99%